IaaS Cloud as a Virtual Environment for Experimentation¡ in Checkpoint Analysis - León, Betzabeth (2019)
Cloud Computing offers the possibility of computing resources, allowing remote access to software, storage and data processing through the Internet. Infrastructures as a Service (IaaS), it is a flexible space which can be used as an experimental environment, in which experiments can be carried out similar to a real environment, such as in a cluster can be carried out. Before making installations and changes in a production cluster or select resource in the cloud, it is important to analyze the impact of this change. For this reason we propose using the cloud to carry out the study of previous viability. In this paper, we observe the viability of using the cloud to analyze the behavior of the Checkpoint as one of the Fault Tolerance strategies, establishing the differences that exist in the information generated in a real environment (cluster) and a virtual environment (cloud). The results obtained show that due to the variability of the cloud, the impact on the benefits cannot be analyzed. However, the cloud is suitable for extracting the spatial and temporal behavior pattern of the checkpoint, which helps to characterize it and this will help us to know the right configuration and the development of methodologies and tools that simulate and predict the execution of the checkpoint in a real environment.